“PENGARUH CORPORATE SOCIAL RESPONSIBILITY, UKURAN PERUSAHAN, KINERJA KEUANGAN, MARKET SHARE DAN STRUKTUR KEPEMILIKAN TERHADAP RESPON INVESTOR “ (STUDI PERUSAHAAN SEKTOR RETAIL YANG TERDAFTAR DI BEI - Kms Agus Riva'i (AKT 16 UMY 186, 2016)
This study aims to examine the influence of Corporate Social Responsibility, company size, financial performance, Market Share, and ownership structure response to investor (study at LISTED retail sector companies on the Indonesia Stock Exchange). The sample in this study were obtained by using purposive sampling method. This study uses secondary data from the annual financial statements published by the Indonesia Stock Exchange and historical price published by www.idx.co.id . There are 66 annual reports and historical price that the research sample during 2011-2014. Hypothesis testing is done by using multiple regression analysis. The results showed that the liquidity, return on assets (ROA) and institutional ownership positively affects investor response. Debt to equty (DER) negatively affect investor response. While corporate social responsibility and market share did not affect the response of investors. Keywords: Corporate Social Responsibility, company size, liquidity, return on assets, debt to equity, Market Share, and ownership structure, Investor response.